GAMBARAN AKTIVITAS FISIK PADA WANITA PASCAMENOPAUSE DI PANTI SOSIAL TRESNA WERDHA KHUSNUL KHOTIMAH PEKANBARU - Helni Sipayung; Eka Bebasari; Miftah Azrin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTDecreased estrogen will be followed by physical and psychological disorder that causes physical activity of postmenopausal woman tend to be limited even depend on others. Descriptive study with cross sectional approach was conducted to identify the physical activity of postmenopausal women in nursing home Khusnul Khotimah Pekanbaru. The instrument study used Barthel Activity of Daily Living and modification of Baecke index questionnaire. Sampel were taken by consecutive sampling tecnique obtaining as many as 27 people respondents aged 56 – 90 years. All of respondents had experienced menopause for over 5 years. Characteristic of postmenopausal women mostly aged 60 - 74 years (66.67%), history of working (62.96%), not have children (51.85%), history of marriage ( 92.60%), not using contraception (92.60%) and no history of chronic disease (59.26%), education level was elementary school (44,44%). The result of this study showed most of postmenopausal women have mild dependence (51,85%) and moderate physical activity (66,66%).Keywords: Baecke index, Barthel index, Physical activity, Postmenopausal